A review of Dengvaxia®: development to deployment. Issue 10 (3rd October 2019) - Thomas, Stephen J.; Yoon, In-Kyu
ABSTRACT: Dengue is the world's most prevalent and important arboviral disease. More than 50% of the world's population lives at daily risk of infection and it is estimated more than 95 million people a year seek medical care following infection. Severe disease can manifest as plasma leakage and potential for clinically significant hemorrhage, shock, and death. Treatment is supportive and there is currently no licensed anti-dengue virus prophylactic or therapeutic compound. A single dengue vaccine, Sanofi Pasteur's Dengvaxia®, has been licensed in 20 countries but uptake has been poor. A safety signal in dengue seronegative vaccine recipients stimulated an international re-look at the vaccine performance profile, new World Health Organization recommendations for use, and controversy in the Philippines involving the government, regulatory agencies, Sanofi Pasteur, clinicians responsible for testing and administering the vaccine, and the parents of vaccinated children. In this review, we provide an overview of Dengvaxia's® development and discuss what has been learned about product performance since its licensure.